Vibration Behavior during Underground Drilling Based on an Innovative Measurement Method and the Application - Peng Cheng; Wenlong Zhang; Wenzhou Li; Jie He; Youliang Feng (Shock and Vibration)
Pressure relief drilling is one of the most common techniques to reduce the impact of rock burst, but the useful dynamic phenomena in the drilling process are ignored due to the lack of corresponding technical methods. Based on the fact, an innovative measurement method for vibration signals during the drilling construction by pneumatic drill rig is presented in this study. The acquisition and analysis of vibration signals show that the vibration information can reflect the drilling depth, the amplitude of different depth can reflect the pressure, and the vibration events of different depths can reflect the pressure relief effect. The method proposed in the study is of great significance to the supervision of the relief work quantity, the disclosure of the pressure situation, and the evaluation of the pressure relief effect.